Georgia Architectural and Historic Properties Survey of Morven [013] Hitch St. Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Morven [013] Hitch St. Quitman, Ga. December 1980. One story house of rectangular plan. Multi-gabled roof. Exposed rafters. Square posts at shed porch. Shiplap siding. Double hung sash windows with 4/4 lights. Exterior chimney. Transom. Brick piers. Poor condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area not extensive enough historically.
Georgia Architectural and Historic Properties Survey of Morven [013] Hitch St. Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.05 MB (1,102,910 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Morven, Ga.; Lowndes Co. (Ga.); Hahira (Ga.)